2006
DOI: 10.1111/j.1744-7348.2006.00102.x
|View full text |Cite
|
Sign up to set email alerts
|

Discrimination between agricultural management and the hedge effect in pear orchards (south‐eastern France)

Abstract: International audienceno abstrac

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(15 citation statements)
references
References 23 publications
1
12
0
Order By: Relevance
“…Roughly in the last decade this concern, along with an increased availability of GIS software packages and tools for landscape analysis (Altobelli et al 2006;Botequila Leitão et al 2006), led to a considerable amount of research regarding the effects of landscape variables on conservation biological control Tscharntke et al 2005Tscharntke et al , 2007. While the majority of investigations concerning this topic are set in arable fields (Bianchi et al 2005;Clough et al 2005;Purtauf et al 2005;Thies et al 2003), only few studies have focused on tree crops (Debras et al 2006). While annual and other arable crops undergo cyclical severe disturbance, which generally implies the complete destruction of the vegetation cover by means of ploughing, tree crops are usually subject to a lower degree of disturbance: weed control is often not carried out on the whole cropping unit, soil is less-intensively disturbed (i.e.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Roughly in the last decade this concern, along with an increased availability of GIS software packages and tools for landscape analysis (Altobelli et al 2006;Botequila Leitão et al 2006), led to a considerable amount of research regarding the effects of landscape variables on conservation biological control Tscharntke et al 2005Tscharntke et al , 2007. While the majority of investigations concerning this topic are set in arable fields (Bianchi et al 2005;Clough et al 2005;Purtauf et al 2005;Thies et al 2003), only few studies have focused on tree crops (Debras et al 2006). While annual and other arable crops undergo cyclical severe disturbance, which generally implies the complete destruction of the vegetation cover by means of ploughing, tree crops are usually subject to a lower degree of disturbance: weed control is often not carried out on the whole cropping unit, soil is less-intensively disturbed (i.e.…”
Section: Introductionmentioning
confidence: 97%
“…Moreover, many studies analyse landscape effects on generalist predators (Debras et al 2006;Purtauf et al 2005;Schmidt et al 2005;Weibull et al 2003), minor crop pests (Ö stman et al 2001;Roschewitz et al 2005) or model systems based on non-crop plants (Elziga et al 2007;Rand and Tscharntke 2007), therefore contributing very little concrete knowledge to the biological control of key pests with widely recognized economic relevance.…”
Section: Introductionmentioning
confidence: 99%
“…A previous study by Miliczky and Horton [2005] proved that diverse wild plant life around an orchard is a favourable habitat for advantageous entomofauna and positively influences its occurrence in agrocenoses. Also Debras et al [2006] indicated a positive correlation between a varied plant life of hedges in the vicinity of pear orchards and the entomophages in those orchards. A similar conclusion was reached by Dib et al [2012], who found a positive impact of flowering plant belts near apple orchards on the occurrence of parasitoids which control the abundance of diapausing Cydia pomonella larvae in orchards.…”
Section: Discussionmentioning
confidence: 88%
“…A positive impact of orchard edge plants onto the occurrence of entomophages in the orchard habitat was proven in the papers by e.g. Piekarska-Boniecka and Suder-Byttner [2002], Debras et al [2006] and Dib et al [2012].…”
Section: Introductionmentioning
confidence: 99%
“…In orchards the effect of pesticides and pest management regimes on arthropods is well documented for a few taxonomic groups, amongst which are spiders (Pekár, 1999;Miliczky et al, 2000;Brown et al, 2003) and ground-living beetles (Pearsall and Walde, 1995;Labrie et al, 2003) but it is more seldom studied for the total arthropod community (Sauphanor et al, 1993(Sauphanor et al, , 2005Suckling et al, 1999;Brown and Schmitt, 2001;Debras et al, 2006;Simon et al, 2007b). The use of pesticides has a negative effect on hunting spiders (Pekár, 1999), groundliving arthropods (Epstein et al, 2000) and insects parasitising leaf miners (Prokopy et al, 1996) but, surprisingly, the total arthropod diversity or richness of the tree canopy is not or very little affected by the use of broad-spectrum insecticide programmes compared with more environmentally friendly methods (Suckling et al, 1999;Brown and Schmitt, 2001;Simon et al, 2007b).…”
Section: Pesticide Applicationsmentioning
confidence: 99%